Supervisory Styles, Stress, and Decision Making: An Application of Prospect Theory - James Montgomery (STIE Malangkucecwara, 2022)
Abstract The purpose of our paper was to investigate the influence of supervisory styles on the manager's perceived stress and decision making. Supervisory styles are a combination of the leadership dimensions, consideration and initiation structure behaviors, and performance measurements, objective and subjective. We used a within-subjects experimental structure to determine the relative effects of perceived stress while making a decision under each supervisory style as well as relative risk-taking under each supervisory style. We found that managers whose supervisors use considerate leadership styles make riskier decisions than managers whose supervisors use initiates structure leadership styles. Furthermore, managers whose organizations use objective performance measures will report more stress than managers whose organizations use subjective measures. The initiates structure with objective performance measures supervisory style induced more perceived stress and resulted in lower risk-taking by the subjects than the other supervisory style combinations. Our research provides evidence that combinations of team-level leadership and organization level performance measures combine to produce unintended outcomes from the firm's managers.